The Spatial Transcriptional Activity of Hepatic TCF7L2 Regulates Zonated Metabolic Pathways that Contribute to Liver Fibrosis - Iriscilla Ayala; Skanda K. Hebbale; Juho Mononen; Madelaine C. Brearley-Sholto; Christopher E. Shannon; Ivan Valdez; Marcel Fourcaudot; Terry M. Bakewell; Anna Zagorska; Giovanna Romero; Mara Asmis; Fatima A. Musa; et al. (Nature Communications)
Abstract The molecular mechanisms regulating the zonal distribution of metabolism in liver are incompletely understood. Here we use single nuclei genomics techniques to examine the spatial transcriptional function of transcription factor 7-like 2 (TCF7L2) in mouse liver, and determine the consequences of TCF7L2 transcriptional inactivation on the metabolic architecture of the liver and the function of zonated metabolic pathways. We report that while Tcf7l2 mRNA expression is ubiquitous across the liver lobule, accessibility of the consensus TCF/LEF DNA binding motif is restricted to pericentral (PC) hepatocytes in zone 3. In mice expressing functionally inactive TCF7L2 in liver, PC hepatocyte-specific gene expression is absent, which we demonstrate promotes hepatic cholesterol accumulation, impaired bile acid synthesis, disruption to glutamine/glutamate homeostasis and pronounced dietary-induced hepatic fibrosis. In summary, TCF7L2 is a key regulator of hepatic zonal gene expression and regulates several zonated metabolic pathways that may contribute to the development of fibrotic liver disease.